Perancangan Sistem Informasi Platform Manajemen Rantai Pasok dengan Metode Design Thinking pada Usaha Mikro Kecil dan Menengah (UMKM) menggunakan Payment Gateway Midtrans - Nur Azizah; Widhy Hayuhardhika Nugraha Putra; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
MSME income affects Indonesia's state finances. However, in the product marketing process, there are many obstacles, one of which is the location of MSMEs that affect consumer interest in the product. In addition, the Covid-19 pandemic has hampered the buying and selling process directly and affected the income earned by several MSMEs. The process of promoting goods and buying and selling of supply materials and the results of processed MSME products is still carried out offline. With these problems, ADMA Digital Marketing, which is a company that accommodates the sociopreneurship-based inter-SME community, provides a solution, namely the design of information systems. In addition, it cooperates with BAKTIKOMINFO, as one of the benefits of the program from KOMINFO, namely the installation of internet access in remote villages. The design of the information system uses the design thinking method as a balance between user needs, the running business, and the functionality of the technology to be designed. Data collection was done by interviewing several target users to find out the problems experienced by each user with different user backgrounds. From the results of the interview, the problems and needs that are needed by the user will be grouped. After that, the idea was designed as a solution using crazy 8 to describe the appearance of the application based on the study case. The design of the system from the predetermined functional from the existing problems using UML diagrams. There are two users in the system, namely free members and resellers. Free members can buy and sell while resellers can sell goods and become resellers for other MSMEs and get business training classes. The system also adds integration, namely the payment gateway midtrans to facilitate payments in the transaction process. Then after knowing the user flow and the existing system, a wireframe is made which is continued on a high fidelity display as a user interface. Usability testing was carried out using a prototype to find out whether the flow created could be used by the user easily, the existing display made it easier for the user to access, and the features provided had resolved the problems experienced by the user. After testing twice, it underwent several changes related to features and additional information.